AN ANALYSIS OF COHERENCE AND COHESION ON THE STUDENTS’ DESCRIPTIVE WRITING AT SENIOR HIGH SCHOOL IN CIREBON - Siti Wahyuni; Oom Rohmah Syamsudin (Universitas Indraprasta PGRI, 2021)
Abstract: This study aimed to find out the usage of coherence and cohesion on the Students’ Descriptive Texts, especially in ten grader students at state senior high school in Cirebon. This study adopted thematic progression analysis to explore coherence in the students’ Descriptive text. This study was a qualitative study that used content analysis. The technique of collecting data was documentation from 46 students writing descriptive texts. The procedures were firstly collecting data, analyzing data, presenting data, and concluding the result of the study. Based on the analyzed data,1) 46 students’ writing descriptive text had grown the writing as the series of the stage in the descriptive text, using Identification and Description. Then, in analyzing coherence 2) 76% students got the coherence level is good, there are 19% in Fair, there are 2% in Less and 3% in Poor and in analyzing cohesion 3) there are 1052 cohesion markers that consist of 852 findings markers of grammatical cohesion (596 findings markers reference and 256 markers conjunction) and 200 markers of lexical cohesion (200 markers repetition).Keywords: series of stage, coherence, cohesion